2013
DOI: 10.2174/13895575113139990005
|View full text |Cite
|
Sign up to set email alerts
|

6H-Indolo[2,3-b]Quinoxalines: DNA and Protein Interacting Scaffold for Pharmacological Activities

Abstract: 6H-Indolo[2,3-b]quinoxaline, a planar fused heterocyclic compound exhibits a wide variety of pharmacological activities. The mechanism of pharmacological action exerted by these compounds is predominantly DNA intercalation. The thermal stability of the intercalated complex (DNA and 6H-indolo[2,3-b]quinoxaline derivatives) is an important parameter for the elucidation of anticancer, antiviral and other activities. This thermal stability of the 6H-indolo[2,3- b]quinoxaline-DNA complex depends on the type of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…For example, several N-(11H-indeno [1,2-b]quinoxalin-11-ylidene)benzohydrazide derivatives with structures related to IQ-1S were recently reported as a-glucosidase inhibitors (Khan et al, 2014), and other structurally unrelated a-glucosidase inhibitors have been reported to have immunosuppressive and immunomodulatory properties (Willenborg et al, 1992;van den Broek et al, 1996). The indeno [1,2-b]quinoxaline nucleus of IQ-1S is a flat aromatic ring structure (Ghalib et al, 2010), and planar fused heterocyclic compounds can exhibit a wide variety of pharmacological activities, including DNA intercalation and inhibition of topoisomerases I/II (Deady et al, 1997;Moorthy et al, 2013). Although we did not evaluate potential DNAintercalating and topoisomerase-inhibiting properties of IQ-1S, this compound was noncytotoxic at high concentrations (Schepetkin et al, 2012), whereas many DNA intercalators (e.g., ellipticine) and topoisomerase inhibitors are cytotoxic (Cros et al, 1975).…”
Section: Foxp3mentioning
confidence: 99%
“…For example, several N-(11H-indeno [1,2-b]quinoxalin-11-ylidene)benzohydrazide derivatives with structures related to IQ-1S were recently reported as a-glucosidase inhibitors (Khan et al, 2014), and other structurally unrelated a-glucosidase inhibitors have been reported to have immunosuppressive and immunomodulatory properties (Willenborg et al, 1992;van den Broek et al, 1996). The indeno [1,2-b]quinoxaline nucleus of IQ-1S is a flat aromatic ring structure (Ghalib et al, 2010), and planar fused heterocyclic compounds can exhibit a wide variety of pharmacological activities, including DNA intercalation and inhibition of topoisomerases I/II (Deady et al, 1997;Moorthy et al, 2013). Although we did not evaluate potential DNAintercalating and topoisomerase-inhibiting properties of IQ-1S, this compound was noncytotoxic at high concentrations (Schepetkin et al, 2012), whereas many DNA intercalators (e.g., ellipticine) and topoisomerase inhibitors are cytotoxic (Cros et al, 1975).…”
Section: Foxp3mentioning
confidence: 99%
“…16 B220 is also a DNA intercalator. 20 In conclusion, B220 was found to be well tolerated at the dose tested and somewhat radioprotective in whole-body -irradiated mice. As no toxicity from B220 was observed this raises the chance for optimisation of B220 administration in terms of quantity and number of doses over time, something that likely will enhance the protective effects of B220 further.…”
Section: Discussionmentioning
confidence: 77%
“…Quinoxaline derivatives are very important class of nitrogen‐containing heterocycles . They show anticancer, anticonvulsant, antimalarial, anti‐inflammatory, antiamoebic, antioxidant, antidepressant, antiprotozoal, antibacterial, and anti‐HIV activities .…”
Section: Introductionmentioning
confidence: 99%